High-cold-resistance environment-friendly PVC decorative material and application thereof

By modifying the cross-linking network of PVC with bio-based plasticizers and composite fillers, the problems of brittle cracking and insufficient environmental protection in low temperature environments are solved, and a high cold resistance and environmentally friendly PVC decorative materials are achieved.

CN120464111APending Publication Date: 2025-08-12SUZHOU BEST DECORATION NEW MATERIALS
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510839514.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The low-temperature resistance and environmental protection of existing PVC materials need to be further improved, especially in low-temperature environments, where traditional plasticizers have the risk of environmental pollution.

Method used

By introducing modified PVC, bio-based plasticizer and composite filler, a stable Si-O-Si network is formed by cross-linking of thiol groups with trimethoxysilane, and a flexible coordination network is formed with bio-based plasticizer and composite filler. Combining the multi-layer structure of nanomontmorillonite and magnesium hydroxide, an organic-inorganic collaborative cross-linking network is constructed.

Benefits of technology

It significantly improves the low temperature resistance and impact resistance of PVC materials, while achieving environmental protection, reducing the risk of plasticizer migration and material embrittlement temperature, and enhancing the environmental friendliness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-cold-resistance environment-friendly PVC decorative material and application thereof, belongs to the technical field of PVC preparation, and is used for solving the technical problem that the low temperature resistance and the environmental protection property of a PVC material in the prior art need to be further improved. The high-cold-resistance environment-friendly PVC decorative material specifically comprises the following raw materials in parts by weight: 80-100 parts of composite PVC, 8-10 parts of a bio-based plasticizer and 6-10 parts of an auxiliary additive; the preparation method comprises the following steps: modifying montmorillonite by using a silane coupling agent, loading magnesium hydroxide to prepare a composite filler, carrying out ring-opening polymerization, amine end capping and oxidation on cyclotrisiloxane to generate a low-temperature-resistant agent containing an epoxy group, introducing trimethoxysilane into PVC through sulfydryl substitution, carrying out hydrolytic condensation to form a Si-O-Si cross-linked network, and covalently binding the Si-O-Si cross-linked network with the filler and the low-temperature-resistant agent to obtain the low-temperature-resistant PVC composite material. And reacting the epoxidized soybean oil with glycine, and carrying out calcium coordination to generate a bio-based plasticizer, thereby finally preparing the PVC decorative material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC preparation, and in particular to a highly cold-resistant and environment-friendly PVC decorative material and application thereof. Background Art

[0002] The development of PVC decorative materials has made significant progress in low-temperature resistance and environmental sustainability. Early PVC materials were brittle at low temperatures, limiting their use in cold climates. Initial improvements included the addition of plasticizers to increase the flexibility of the chain, but these often compromised environmental safety due to volatility and toxicity. Subsequent progress introduced bio-based plasticizers derived from renewable resources to improve low-temperature toughness by increasing molecular chain mobility while reducing environmental impact. The addition of nanofillers and flexibility modifiers further enhances durability by strengthening interfacial interactions and forming elastic networks, ensuring elasticity in cold conditions. Advances in cross-linking technology create strong, flexible structures that maintain integrity at low temperatures. Recent developments emphasize environmentally friendly additives and renewable materials to achieve low-temperature ductility as well as non-toxicity and reduced emissions, meeting sustainable demands for multifunctional, environmentally friendly PVC decorative applications.

[0003] For example, the prior art CN118909367B discloses a low-temperature resistant PVC plastic and a preparation method thereof, which specifically includes the following raw materials in parts by mass: 100 parts of PVC resin, 30-40 parts of filler, 10-15 parts of low-temperature toughening agent, 3-6 parts of stabilizer, 10-20 parts of plasticizer, and 1-3 parts of lubricant. The low-temperature toughening agent is prepared by free radical copolymerization of comonomers, and the comonomers include styrene-butadiene latex, an organosilicon monomer with an alkenyl group, and an alkyl acrylate monomer in a mass ratio of 50-60:15-25:10-20. The number of carbon atoms of the alkyl group in the alkyl acrylate is 2-8, and the styrene content in the styrene-butadiene latex is 15-30%. The prepared PVC plastic has excellent low-temperature resistance, is not easy to crack in low-temperature environments, and has good durability.

[0004] However, the above patent content is to improve the low-temperature resistance of the material by introducing a low-temperature toughening agent, but the low-temperature toughening relies on emulsion copolymer particles, which contain thermoplastic elastomers such as styrene-butadiene latex. It does have a certain softening effect on PVC, but its mode of action is physical mixing and partial polar association. As time and temperature fluctuate, the microphase interface may precipitate or rupture. Although silicone and hydroxy acrylate are introduced into the copolymer monomer, the chain segments fail to be effectively cross-linked or locked on the PVC main chain, resulting in unstable low-temperature resistance. In addition, traditional monomers such as petrochemical-based acrylates and styrene-butadiene latex are still used, resulting in the material's low-temperature resistance and environmental performance need to be further improved. Summary of the Invention

[0005] The purpose of the present invention is to provide a highly cold-resistant and environmentally friendly PVC decorative material and its application, so as to solve the technical problem in the prior art that the low-temperature resistance and environmental protection of PVC materials need to be further improved.

[0006] The object of the present invention can be achieved by the following technical solution: A highly cold-resistant and environmentally friendly PVC decorative material, comprising the following raw materials in parts by weight: 80-100 parts of composite PVC, 8-10 parts of bio-based plasticizer and 6-10 parts of auxiliary additives; Furthermore, the auxiliary additive comprises the following raw materials in parts by weight: 2-3 parts of calcium stearate, 1-2 parts of tris(2,4-di-tert-butylphenyl)phosphate, 2-3 parts of 2-hydroxy-4-octyloxybenzophenone and 1-2 parts of montan wax; Furthermore, the preparation method of the composite PVC comprises the following steps: A1. Add PVC powder, 1,2-ethanedithiol, mercaptopropyltrimethoxysilane, and N,N-dimethylformamide to a reactor. After the reactor temperature is raised to 100-110°C, stir until the reactants are completely dissolved. Then, add tetrabutylammonium bromide to the reactor, keep the temperature and stir for 4-6 hours, and perform post-treatment to obtain modified PVC. A2. Add modified PVC, deionized water and N,N-dimethylformamide into a reactor. Use saturated sodium hydroxide aqueous solution to adjust the pH of the reaction system to 8-10. Then, raise the temperature of the reactor to 70-80°C. Keep warm and stir until the reactants are dissolved. Then, add low-temperature resistant agent and composite filler into the reactor. Keep warm and stir for 1-2 hours. After post-treatment, obtain composite PVC.

[0007] The reaction principle for preparing composite PVC is as follows: Tetrabutylammonium bromide acts as a phase transfer catalyst, promoting effective contact between the nucleophilic reagent and the PVC reaction interface. This allows the active chlorine atoms on the PVC molecular chain to be nucleophilically replaced by thiol groups under heating conditions. The thiol groups in both 1,2-ethanedithiol and mercaptopropyltrimethoxysilane can attack the C-Cl bond, replacing the chlorine atoms with the thiol groups. This crosslinks the chain segments and introduces a trimethoxysilane structure to produce modified PVC. The -Si(OCH3)3 in the introduced trimethoxysilane structure hydrolyzes in an alkaline aqueous solution to form -Si(OH)3. The hydrolyzed silanol further undergoes a condensation reaction to form Si-O-Si bonds. This crosslinked structure simultaneously condenses with the hydroxyl groups in the composite filler and the epoxy groups in the low-temperature resistant agent, forming a stable covalent or physical network to produce composite PVC.

[0008] Furthermore, in the process of preparing composite PVC, in step A1, the amount ratio of PVC powder, 1,2-ethanedithiol, mercaptopropyltrimethoxysilane, N,N-dimethylformamide and tetrabutylammonium bromide is 8-10g:0.5-0.8g:1-2g:40-50mL:0.3-0.4g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, 2-3 times the volume of deionized water is slowly added to the reactor, and after standing for 2-3 hours, the reaction liquid is filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water 3-5 times, the filter cake is transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain modified PVC; Furthermore, in step A2, the amount ratio of modified PVC, deionized water, N,N-dimethylformamide, low-temperature resistant agent and composite filler is 8-10g:10-12mL:30-40mL:0.5-0.8g:1.2-1.5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator at a temperature of 70-80°C, and evaporated until no liquid is recovered to obtain composite PVC.

[0009] Furthermore, the preparation method of the bio-based plasticizer comprises the following steps: B1. Add epoxidized soybean oil, glycine and dimethyl sulfoxide into a reactor, raise the temperature of the reactor to 60-80°C, keep the temperature for reaction for 1-2 hours, and post-treat to obtain a plasticizer precursor; B2. Add the plasticizer precursor, deionized water and dimethyl sulfoxide into the reactor, increase the temperature of the reactor to 50-60°C and use saturated sodium hydroxide aqueous solution to adjust the pH of the reaction system to 8-10, then add calcium chloride into the reactor, keep the temperature and react for 40-60 minutes, and post-treat to obtain the bio-based plasticizer.

[0010] The reaction principle for preparing the bio-based plasticizer is as follows: the epoxy group in the epoxidized soybean oil molecule undergoes a nucleophilic attack by the amino group of glycine under elevated temperature conditions, resulting in a ring-opening reaction to generate a plasticizer precursor containing hydroxyl and amino acid groups; the carboxyl group introduced in the plasticizer precursor is ionized into a carboxylate under alkaline conditions. Under alkaline conditions, after adding calcium chloride, the ionized Ca2+ coordinates with the carboxylate to form a stable calcium complex structure, thereby obtaining the bio-based plasticizer.

[0011] Furthermore, in step B1, the ratio of epoxy soybean oil, glycine and dimethyl sulfoxide is 7-8 g: 1-2 g: 30-36 mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, ethyl acetate is added to extract the organic phase, the organic phase is dried with anhydrous sodium sulfate, and the organic phase is transferred to a rotary evaporator at a temperature of 70-80° C. and evaporated until no liquid is recovered to obtain a plasticizer precursor; Furthermore, in step B2, the ratio of the amount of plasticizer precursor, deionized water, dimethyl sulfoxide and calcium chloride is 8-10g:10-15mL:25-30mL:1-2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to a rotary evaporator at a temperature of 70-80°C, and evaporated until no liquid is collected to obtain a bio-based plasticizer.

[0012] Furthermore, the preparation method of the low temperature resistant agent comprises the following steps: C1. Add 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, trifluoropropylmethylcyclotrisiloxane and N,N-dimethylformamide to a reactor. After the temperature of the reactor is raised to 100-120° C., add sodium hydroxide to the reactor. After keeping the temperature for 4-5 hours, add 1,1,3,3-tetramethyldisiloxane-1,3-diamine to the reactor. Keep the temperature for 2-3 hours, and perform post-treatment to obtain modified polysiloxane. C2. Add modified polysiloxane and N,N-dimethylformamide into a reactor, introduce nitrogen protection, lower the temperature of the reactor to 10-15°C, add m-chloroperbenzoic acid into the reactor, keep the temperature for reaction for 1-2 hours, and post-treat to obtain a low-temperature resistant agent.

[0013] The reaction equation for preparing the low-temperature resistant agent is:

[0014] Where: .

[0015] The reaction principle for preparing the low-temperature resistant agent is as follows: under the catalysis of sodium hydroxide, the Si-O bonds of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane and trifluoropropylmethylcyclotrisiloxane are opened to form a linear polysiloxane chain, which is then capped with 1,1,3,3-tetramethyldisiloxane-1,3-diamine to obtain a modified polysiloxane; and meta-chloroperbenzoic acid undergoes an oxidation reaction with the vinyl groups on the modified polysiloxane at low temperatures to form a three-membered ring epoxy group, thereby preparing the low-temperature resistant agent.

[0016] Furthermore, in step C1, the amount ratio of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, trifluoropropylmethylcyclotrisiloxane, N,N-dimethylformamide, sodium hydroxide and 1,1,3,3-tetramethyldisiloxane-1,3-diamine is 4-5g:6-8g:50-54mL:0.3-0.5g:1-2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is transferred to a rotary evaporator at a temperature of 100-120°C, and after evaporation until no liquid is produced, the material is transferred to anhydrous ethanol, and after standing for 1-2h, the precipitate is collected by filtration, and the precipitate is transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a modified polysiloxane; Furthermore, in step C2, the amount ratio of modified polysiloxane, N,N-dimethylformamide and m-chloroperbenzoic acid is 6-8g:20-24mL:1-2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is raised to room temperature, sodium bicarbonate is used to adjust the reaction system to neutral, and the organic phase is extracted with ethyl acetate, and the organic phase is transferred to a rotary evaporator at a temperature of 70-80°C, and evaporated until no liquid is extracted to obtain a low-temperature resistant agent.

[0017] Furthermore, the preparation method of the composite filler comprises the following steps: D1. Add nano-montmorillonite, composite solvent and γ-methacryloxypropyltrimethoxysilane to a reactor. After the temperature of the reactor is raised to 40-60° C., adjust the pH of the reaction system to 4-5 with acetic acid, keep the reaction mixture warm and stir for 1-2 hours, and perform post-treatment to obtain modified montmorillonite. D2. Add modified montmorillonite and deionized water into a reactor, add magnesium chloride into the reactor under stirring, adjust the pH of the reaction system to 10-11 with a protective sodium hydroxide aqueous solution after the addition, stir at room temperature for 60-80 minutes, and post-treat to obtain a composite filler.

[0018] The reaction principle for preparing the composite filler is as follows: under acidic conditions, the methoxy group of gamma-methacryloyloxypropyltrimethoxysilane is hydrolyzed into silanol to form an active intermediate, and condensation occurs between the hydrolyzed silanols and between the silanols and the hydroxyl groups on the surface of montmorillonite to form Si-O-Si- bonds or Si-OM (M is a metal ion on the surface of montmorillonite) bonds. At the same time, the organosilane molecules are embedded in the montmorillonite layer structure through intermolecular interactions to form an intercalation or coating structure; magnesium chloride is ionized into Mg2+ in water and undergoes complexation or ion exchange with the negative charge sites in the montmorillonite structure; under alkaline conditions, Mg2+ reacts with OH- to form magnesium hydroxide precipitate; the precipitated magnesium hydroxide is uniformly attached or deposited on the surface of the modified montmorillonite or the interlayer space under stirring conditions to form a composite structure, thereby preparing the composite filler.

[0019] Furthermore, in step D1, the amount ratio of nano-montmorillonite, composite solvent and γ-methacryloxypropyltrimethoxysilane is 1-2g:10-12mL:0.1-0.2g, wherein the composite solvent is anhydrous ethanol and deionized water mixed in an amount ratio of 8-10mL:3-4mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water 3-5 times, the filter cake is transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain modified montmorillonite; Furthermore, in step D2, the ratio of modified montmorillonite, deionized water and magnesium chloride is 1-2g:10-12mL:0.2-0.4g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing it with anhydrous ethanol and deionized water 3-5 times, the filter cake is transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a composite filler.

[0020] Furthermore, the preparation method of the PVC decorative material is: adding composite PVC, bio-based plasticizer, heat stabilizer, antioxidant, light stabilizer and lubricant into a melt extruder, melt-extrude into a mold, and naturally cool to room temperature to obtain the PVC decorative material.

[0021] Furthermore, the parameters of the melt extruder are set as follows: hopper zone temperature is 150-155°C, compression zone is 160-165°C, metering zone is 165-170°C, die zone is 160-165°C and screw speed is 40-60 rpm.

[0022] The present invention also proposes an application of a highly cold-resistant and environmentally friendly PVC decorative material, which is used to prepare decorative items for use in high-altitude and low-temperature areas.

[0023] The present invention has the following beneficial effects: 1. The modified polysiloxane molecular chain introduced into the PVC chain segment of the present invention has a soft Si-O skeleton structure with a glass transition temperature much lower than that of the PVC body, which helps to improve the mobility of the chain segment at low temperatures, thereby avoiding embrittlement caused by chain stiffness. At the same time, the epoxy structure in the polysiloxane can form multi-point crosslinks with other components, enhancing the overall flexibility and low-temperature resistance of the system. Secondly, through the modification of the PVC molecular chain with thiol groups, a crosslinkable trimethoxysilane structure is introduced. In an alkaline environment, it hydrolyzes to form silanols, which further condense to form a stable Si-O-Si network. This network structure not only maintains the strength of the intermolecular connection under low temperature conditions, but also effectively alleviates the microscopic stress concentration caused by cold shrinkage. In addition, the bio-based plasticizer contains polar hydroxyl groups and calcium complex structures, which can form a flexible coordination network with the PVC chain segment. This structure can continuously exert the chain segment lubrication and softening effect at low temperatures, further inhibiting the glass transition of the material and significantly reducing its brittleness temperature, thereby significantly improving the low-temperature resistance of the PVC material.

[0024] 2. The present invention forms a dense organic network through cross-linking reaction by introducing mercapto and trimethoxysilane structures into the PVC main chain, thereby improving the connection strength between polymer chains and effectively preventing the expansion of microcracks. Secondly, the polysiloxane chain segment itself has flexibility and can absorb part of the stress and quickly buffer and disperse it when subjected to force impact, reducing local stress concentration. The amino group in the low-temperature resistant agent enhances the reactivity of the PVC chain segment with the bio-based plasticizer. At the same time, the composite filler of magnesium hydroxide and montmorillonite plays a "skeleton" role in the microstructure. Its lamellar structure can disperse the impact force path, delay crack propagation, and form a stable interface with the organic phase. In particular, the filler modified with silane coupling agent forms a chemical bond with the PVC matrix, significantly increasing the interfacial energy, thereby preventing interfacial peeling under impact. Ultimately, the synergistic structure of organic flexible chains, inorganic rigid fillers and cross-linked networks gives the material excellent energy absorption and structural retention capabilities, thereby significantly improving the material's impact resistance.

[0025] 3. The present invention eliminates the risk of harmful substance release by introducing bio-based plasticizers to replace traditional o-phthalate plasticizers. The carboxylate introduced into its molecular structure forms a stable complex with calcium ions, which enhances the interaction between molecules and inhibits the migration of plasticizers. In addition, during the preparation process, the multi-layer structure of montmorillonite in the composite filler allows hydrogen chloride gas to be retained while the dispersed magnesium hydroxide structure absorbs and decomposes to produce hydrogen chloride gas, thereby ensuring the environmental friendliness of the material at the source. Secondly, the mercapto group undergoes a cross-linking reaction with the PVC molecular chain, introducing a silane structural unit into the system, further The first step is to generate Si-O-Si bonds through hydrolysis and condensation, which condense with the hydroxyl groups on the surface of montmorillonite and the epoxy groups on the polysiloxane to build an organic-inorganic synergistic cross-linking network, which not only improves the density of the material structure, but also significantly inhibits the generation of microscopic wear particles; and the layered structure of magnesium hydroxide and montmorillonite provides a physical barrier for the material, reducing the accumulation of frictional heat and the probability of chain segment breakage. At the same time, the polysiloxane segment gives it a certain flexibility and resilience, so that the stress generated during the wear process can be evenly released, ultimately making the material achieve green and environmental protection goals while also significantly improving wear resistance. DETAILED DESCRIPTION

[0026] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0027] The PVC powder used in the present invention was purchased from MacLean Biochemical Technology Co., Ltd., with the product number P708201; The calcium stearate used in the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with the product number C805417-1kg. The epoxidized soybean oil used in the present invention was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with the product number B25760-250mg; The montan wax used in the present invention is purchased from Shanghai MacLean Biochemical Technology Co., Ltd., M723187-2.5 kg.

[0028] Example 1 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly composite filler for use in preparing PVC decorative materials, comprising the following steps: Step ①, preparation of modified montmorillonite Weigh: 80.0 mL of anhydrous ethanol and 30.0 mL of deionized water and mix to obtain a composite solvent; 10.0 g of nano-montmorillonite, 100.0 mL of composite solvent and 1.0 g of γ-methacryloxypropyltrimethoxysilane were weighed and added to a reactor. After the temperature of the reactor was raised to 40° C., the pH of the reaction system was adjusted to 5 using acetic acid, and the mixture was stirred for 1 h. Modified montmorillonite was obtained by post-treatment.

[0029] Step 2: Preparation of composite filler Weigh: 10.0g modified montmorillonite and 100.0mL deionized water were added to the reactor, and 2.0g magnesium chloride was added to the reactor under stirring. After the addition was completed, the pH of the reaction system was adjusted to 10 with a protective sodium hydroxide aqueous solution, and stirred at room temperature for 60min. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and it was washed 3 times with anhydrous ethanol and deionized water. The filter cake was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a composite filler.

[0030] Example 2 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly composite filler for use in preparing PVC decorative materials, comprising the following steps: Step ①, preparation of modified montmorillonite Weigh: 100.0 mL of anhydrous ethanol and 40.0 mL of deionized water and mix to obtain a composite solvent; 20.0 g of nano-montmorillonite, 120.0 mL of composite solvent and 2.0 g of γ-methacryloxypropyltrimethoxysilane were weighed and added to a reactor. After the temperature of the reactor was raised to 60° C., the pH of the reaction system was adjusted to 5 using acetic acid, and the mixture was stirred for 2 h at this temperature. Modified montmorillonite was obtained by post-treatment.

[0031] Step 2: Preparation of composite filler Weigh: 20.0g modified montmorillonite and 120.0mL deionized water were added to the reactor, and 4.0g magnesium chloride was added to the reactor under stirring. After the addition was completed, the pH of the reaction system was adjusted to 11 using a protective sodium hydroxide aqueous solution and stirred at room temperature for 80 minutes. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water 5 times, the filter cake was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a composite filler.

[0032] Example 3 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly composite filler for use in preparing PVC decorative materials, comprising the following steps: Step ①, preparation of modified montmorillonite Weigh: 96.0 mL of anhydrous ethanol and 36.0 mL of deionized water to make a composite solvent; 16.0 g of nano-montmorillonite, 120.0 mL of composite solvent and 1.6 g of γ-methacryloxypropyltrimethoxysilane were weighed and added to a reactor. After the temperature of the reactor was raised to 50° C., acetic acid was used to adjust the pH of the reaction system to 4, and the mixture was stirred for 2 h. Modified montmorillonite was obtained by post-treatment.

[0033] Step 2: Preparation of composite filler Weigh: 15.0g modified montmorillonite and 120.0mL deionized water were added to the reactor, and 3.6g magnesium chloride was added to the reactor under stirring. After the addition was completed, the pH of the reaction system was adjusted to 11 using a protective sodium hydroxide aqueous solution. Stir at room temperature for 70 minutes. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, and after washing with anhydrous ethanol and deionized water 4 times, the filter cake was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a composite filler.

[0034] Example 4 This embodiment provides a method for preparing a low-temperature resistant agent for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step (i) Weighing modified polysiloxane Weigh: 40.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 60.0gtrifluoropropylmethylcyclotrisiloxane and 500.0mLN,N-dimethylformamide were added to the reactor. After the temperature of the reactor was raised to 100°C, 3.0gsodium hydroxide was added to the reactor. After the reaction was kept warm for 4 hours, 10.0g1,1,3,3-tetramethyldisiloxane-1,3-diamine was added to the reactor. The reaction was kept warm for 2 hours. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction liquid was transferred to a rotary evaporator at a temperature of 100°C. After evaporation until no liquid was produced, the material was transferred to anhydrous ethanol, allowed to stand for 1 hour, and the precipitate was collected by filtration. The precipitate was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a modified polysiloxane.

[0035] Step 2: Weigh the low-temperature resistant agent Weigh: 60.0g modified polysiloxane and 200.0mL N,N-dimethylformamide are added to the reactor. After nitrogen protection is introduced, the temperature of the reactor is reduced to 10°C, 10.0g of m-chloroperbenzoic acid is added to the reactor, and the reaction is kept warm for 1h. After the reaction is completed, the temperature of the reactor is raised to room temperature, sodium bicarbonate is used to adjust the reaction system to neutral, and the organic phase is extracted with ethyl acetate. The organic phase is transferred to a rotary evaporator at a temperature of 70°C and evaporated until no liquid is extracted to obtain a low-temperature resistant agent.

[0036] Example 5 This embodiment provides a method for preparing a low-temperature resistant agent for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step (i) Weighing modified polysiloxane Weigh: 50.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 80.0gtrifluoropropylmethylcyclotrisiloxane and 540.0mLN,N-dimethylformamide were added to the reactor. After the temperature of the reactor was raised to 120°C, 5.0gsodium hydroxide was added to the reactor. After the reaction was kept warm for 5 hours, 20.0g1,1,3,3-tetramethyldisiloxane-1,3-diamine was added to the reactor. The reaction was kept warm for 3 hours. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction liquid was transferred to a rotary evaporator with a temperature of 120°C. After evaporation until no liquid was produced, the material was transferred to anhydrous ethanol, allowed to stand for 2 hours, and then the precipitate was collected by filtration. The precipitate was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a modified polysiloxane.

[0037] Step 2: Weigh the low-temperature resistant agent Weigh: 80.0g modified polysiloxane and 240.0mL N,N-dimethylformamide are added to the reactor. After nitrogen protection is introduced, the temperature of the reactor is reduced to 15°C, 20.0g of m-chloroperbenzoic acid is added to the reactor, and the reaction is kept warm for 2h. After the reaction is completed, the temperature of the reactor is raised to room temperature, and sodium bicarbonate is used to adjust the reaction system to neutral. The organic phase is extracted with ethyl acetate, and the organic phase is transferred to a rotary evaporator at a temperature of 80°C. After evaporation until no liquid is extracted, a low-temperature resistant agent is obtained.

[0038] Example 6 This embodiment provides a method for preparing a low-temperature resistant agent for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step (i) Weighing modified polysiloxane Weigh: 45.0g2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 72.0gtrifluoropropylmethylcyclotrisiloxane and 510.0mLN,N-dimethylformamide were added to the reactor. After the temperature of the reactor was raised to 120°C, 4.0gsodium hydroxide was added to the reactor. After the reaction was kept warm for 5 hours, 16.0g1,1,3,3-tetramethyldisiloxane-1,3-diamine was added to the reactor. The reaction was kept warm for 3 hours. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction liquid was transferred to a rotary evaporator with a temperature of 120°C. After evaporation until no liquid was produced, the material was transferred to anhydrous ethanol, allowed to stand for 2 hours, and then the precipitate was collected by filtration. The precipitate was transferred to a drying oven at a temperature of 80°C and dried to constant weight to obtain a modified polysiloxane.

[0039] Step 2: Weigh the low-temperature resistant agent Weigh: 70.0g modified polysiloxane and 210.0mL N,N-dimethylformamide are added to the reactor. After nitrogen protection is introduced, the temperature of the reactor is reduced to 12°C, 16.0g of m-chloroperbenzoic acid is added to the reactor, and the reaction is kept warm for 2h. After the reaction is completed, the temperature of the reactor is raised to room temperature, sodium bicarbonate is used to adjust the reaction system to neutral, and the organic phase is extracted with ethyl acetate. The organic phase is transferred to a rotary evaporator at a temperature of 80°C and evaporated until no liquid is extracted to obtain a low-temperature resistant agent.

[0040] Example 7 This embodiment provides a method for preparing a composite PVC for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step Ⅰ: Weigh modified PVC Weigh: 80.0g PVC powder, 5.0g 1,2-ethanedithiol, 10.0g mercaptopropyltrimethoxysilane and 400.0mL N,N-dimethylformamide and add them to the reactor. After the temperature of the reactor is raised to 100°C, stir until the reactants are completely dissolved, add 3.0g tetrabutylammonium bromide to the reactor, and stir for 4 hours. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, slowly add 2 times the volume of deionized water to the reactor, let it stand for 2 hours, filter the reaction liquid to collect the filter cake, and wash it with anhydrous ethanol and deionized water 3 times. Then, transfer the filter cake to a drying oven at 80°C and dry it to constant weight to obtain modified PVC.

[0041] Step II: Weigh the composite PVC Weigh: 80.0 g of modified PVC, 100.0 mL of deionized water and 300.0 mL of N,N-dimethylformamide were added to the reactor, and the pH of the reaction system was adjusted to 8 with a saturated sodium hydroxide aqueous solution. The temperature of the reactor was raised to 70°C, and the mixture was stirred at this temperature until the reactants were dissolved. Then, 5.0 g of the low-temperature resistant agent prepared in Example 4 and 12.0 g of the composite filler prepared in Example 1 were added to the reactor, and the mixture was stirred at this temperature for 1 hour. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction solution was transferred to a rotary evaporator at a temperature of 70°C. After evaporation until no liquid was recovered, composite PVC was obtained.

[0042] Example 8 This embodiment provides a method for preparing a composite PVC for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step Ⅰ: Weigh modified PVC Weigh: 100.0g PVC powder, 8.0g 1,2-ethanedithiol, 20.0g mercaptopropyltrimethoxysilane and 500.0mL N,N-dimethylformamide and add them to the reactor. After the temperature of the reactor is raised to 110°C, stir until the reactants are completely dissolved, add 4.0g tetrabutylammonium bromide to the reactor, and stir for 6 hours. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, slowly add 3 times the volume of deionized water to the reactor, let it stand for 3 hours, filter the reaction liquid to collect the filter cake, and wash it with anhydrous ethanol and deionized water 5 times. Then, transfer the filter cake to a drying oven at 80°C and dry it to constant weight to obtain modified PVC.

[0043] Step II: Weigh the composite PVC Weigh: 100.0 g modified PVC, 120.0 mL deionized water and 400.0 mL N, N-dimethylformamide were added to the reactor, and the pH of the reaction system was adjusted to 10 with a saturated sodium hydroxide aqueous solution. The temperature of the reactor was raised to 80 ° C. and stirred until the reactants were dissolved. Then, 8.0 g of the low-temperature resistant agent prepared in Example 5 and 15.0 g of the composite filler prepared in Example 2 were added to the reactor. The mixture was stirred for 2 hours. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction solution was transferred to a rotary evaporator at a temperature of 80 ° C. and evaporated until no liquid was recovered to obtain composite PVC.

[0044] Example 9 This embodiment provides a method for preparing a composite PVC for preparing a highly cold-resistant and environmentally friendly PVC decorative material, comprising the following steps: Step Ⅰ: Weigh modified PVC Weigh: 90.0g PVC powder, 7.2g 1,2-ethanedithiol, 15.0g mercaptopropyltrimethoxysilane and 450.0mL N,N-dimethylformamide and add them to the reactor. After the temperature of the reactor is raised to 110°C, stir until the reactants are completely dissolved, add 3.6g tetrabutylammonium bromide to the reactor, and stir for 5 hours. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, slowly add 3 times the volume of deionized water to the reactor, let it stand for 3 hours, filter the reaction liquid to collect the filter cake, and wash it with anhydrous ethanol and deionized water 4 times. Then, transfer the filter cake to a drying oven at 80°C and dry it to constant weight to obtain modified PVC.

[0045] Step II: Weigh the composite PVC Weigh: 90.0g modified PVC, 100.0mL deionized water and 400.0mL N,N-dimethylformamide were added to the reactor, and the pH of the reaction system was adjusted to 9 with saturated sodium hydroxide aqueous solution. The temperature of the reactor was raised to 75°C, and the mixture was stirred at this temperature until the reactants were dissolved. Then, 6.4g of the low-temperature resistant agent prepared in Example 6 and 15.0g of the composite filler prepared in Example 3 were added to the reactor, and the mixture was stirred at this temperature for 2h. After the reaction was completed, the temperature of the reactor was lowered to room temperature, and the reaction solution was transferred to a rotary evaporator at a temperature of 75°C. After evaporation until no liquid was recovered, composite PVC was obtained.

[0046] Example 10 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly PVC decorative material, comprising the following steps: Step 1: Preparation of bio-based plasticizer Weigh: 80.0 g of epoxidized soybean oil, 10.0 g of glycine and 300.0 mL of dimethyl sulfoxide were added to a reactor, the reactor temperature was raised to 60° C., and the reaction was kept warm for 1 hour. After the reaction was completed, the reactor temperature was lowered to room temperature, ethyl acetate was added to extract the organic phase, and the organic phase was dried over anhydrous sodium sulfate. The organic phase was transferred to a rotary evaporator at a temperature of 70° C. and evaporated until no liquid was recovered to obtain a plasticizer precursor; Weigh: 80.0 g of plasticizer precursor, 100.0 mL of deionized water and 250.0 mL of dimethyl sulfoxide were added to the reactor, the reactor temperature was raised to 50°C and the pH of the reaction system was adjusted to 8 using a saturated sodium hydroxide aqueous solution, and then 10.0 g of calcium chloride was added to the reactor. The reaction was kept warm for 40 minutes. After the reaction was completed, the reactor temperature was lowered to room temperature, and the reaction liquid was transferred to a rotary evaporator at a temperature of 70°C. After evaporation until no liquid was recovered, a bio-based plasticizer was obtained.

[0047] Step 2: Prepare PVC decorative materials In parts by weight, 80 parts of the composite PVC prepared in Example 7, 8 parts of a bio-based plasticizer, 2 parts of calcium stearate, 1 part of tris(2,4-di-tert-butylphenyl)phosphate, 2 parts of 2-hydroxy-4-octyloxybenzophenone and 1 part of montan wax were weighed and added to a melt extruder. The temperature of the hopper zone of the melt extruder was 150° C., the compression zone was 160° C., the metering zone was 165° C., the die zone was 160° C., and the screw speed was 40 rpm. The mixture was melt-extruded into a mold and naturally cooled to room temperature to obtain a PVC decorative material.

[0048] Example 11 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly PVC decorative material, comprising the following steps: Step 1: Preparation of bio-based plasticizer Weigh: 80.0 g of epoxidized soybean oil, 20.0 g of glycine and 360.0 mL of dimethyl sulfoxide were added to a reactor, the reactor temperature was raised to 80° C., and the reaction was kept warm for 2 hours. After the reaction was completed, the reactor temperature was lowered to room temperature, ethyl acetate was added to extract the organic phase, and the organic phase was dried over anhydrous sodium sulfate. The organic phase was transferred to a rotary evaporator at a temperature of 80° C. and evaporated until no liquid was recovered to obtain a plasticizer precursor; Weigh: 90.0 g of plasticizer precursor, 150.0 mL of deionized water and 300.0 mL of dimethyl sulfoxide were added to the reactor, the reactor temperature was raised to 60°C and the pH of the reaction system was adjusted to 10 using a saturated sodium hydroxide aqueous solution, and then 20.0 g of calcium chloride was added to the reactor. The reaction was kept warm for 60 minutes. After the reaction was completed, the reactor temperature was lowered to room temperature, and the reaction liquid was transferred to a rotary evaporator at 80°C. After evaporation until no liquid was recovered, a bio-based plasticizer was obtained.

[0049] Step 2: Prepare PVC decorative materials In parts by weight, 100 parts of the composite PVC prepared in Example 8, 10 parts of a bio-based plasticizer, 3 parts of calcium stearate, 2 parts of tris(2,4-di-tert-butylphenyl)phosphate, 3 parts of 2-hydroxy-4-octyloxybenzophenone and 2 parts of montan wax were weighed and added to a melt extruder. The temperature of the hopper zone of the melt extruder was 155°C, the compression zone was 165°C, the metering zone was 170°C, the die zone was 165°C and the screw speed was 60 rpm. The mixture was melt-extruded into a mold and naturally cooled to room temperature to obtain a PVC decorative material.

[0050] Example 12 This embodiment provides a method for preparing a highly cold-resistant, environmentally friendly PVC decorative material, comprising the following steps: Step 1: Preparation of bio-based plasticizer Weigh: 80.0 g of epoxidized soybean oil, 16.0 g of glycine and 320.0 mL of dimethyl sulfoxide were added to a reactor, the reactor temperature was raised to 80° C., and the reaction was kept warm for 2 hours. After the reaction was completed, the reactor temperature was lowered to room temperature, ethyl acetate was added to extract the organic phase, and the organic phase was dried over anhydrous sodium sulfate. The organic phase was transferred to a rotary evaporator at a temperature of 80° C. and evaporated until no liquid was recovered to obtain a plasticizer precursor; Weigh: 80.0 g of plasticizer precursor, 120.0 mL of deionized water and 280.0 mL of dimethyl sulfoxide were added to the reactor, the reactor temperature was raised to 60°C and the pH of the reaction system was adjusted to 9 using a saturated sodium hydroxide aqueous solution. Then, 15.0 g of calcium chloride was added to the reactor and the reaction was kept warm for 50 minutes. After the reaction was completed, the reactor temperature was lowered to room temperature and the reaction liquid was transferred to a rotary evaporator at 75°C. After evaporation until no liquid was recovered, a bio-based plasticizer was obtained.

[0051] Step 2: Prepare PVC decorative materials In parts by weight, 96 parts of the composite PVC prepared in Example 9, 9 parts of a bio-based plasticizer, 2 parts of calcium stearate, 2 parts of tris(2,4-di-tert-butylphenyl)phosphate, 2 parts of 2-hydroxy-4-octyloxybenzophenone and 2 parts of montan wax were weighed and added to a melt extruder. The temperature of the hopper zone of the melt extruder was 155°C, the compression zone was 160°C, the metering zone was 165°C, the die zone was 165°C and the screw speed was 50 rpm. The mixture was melt-extruded into a mold and naturally cooled to room temperature to obtain a PVC decorative material.

[0052] Comparative Example 1 The difference between this comparative example and Example 12 is that the bio-based plasticizer is eliminated in step 2 and replaced with an equal amount of plasticizer precursor.

[0053] Comparative Example 2 The difference between this comparative example and Example 12 is that the composite filler is not used during the preparation of the composite PVC used in the steps.

[0054] Comparative Example 3 The difference between this comparative example and Example 12 is that the low-temperature resistant agent is not used during the preparation of the composite PVC used in the steps.

[0055] Performance testing: The low-temperature resistance of the PVC decorative materials prepared in Examples 10-12 and Comparative Examples 1-3 was measured with reference to the standard GB / T 5470-2008 "Determination of Brittleness Temperature of Plastics by Impact Method"; The volume abrasion loss of the PVC decorative materials prepared in Examples 10-12 and Comparative Examples 1-3 was measured in accordance with the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)"; The Izod impact strength of the composite polyvinyl chloride prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1843-2008 “Determination of Izod Impact Strength of Plastics”; The acid gas emissions during the production of the PVC decorative materials prepared in Examples 10-12 and Comparative Examples 1-3 were measured with reference to Standard HJ 549-2016 “Determination of Hydrogen Chloride in Ambient Air and Waste Gas - Ion Chromatography”. Specific data are shown in Table 1.

[0056] Table 1 - Performance test data of each sample

[0057] Data Analysis: After comparing and analyzing the data in Table 1, it can be found that the composite PVC prepared by the present invention has a catalytic temperature of -63°C, a volumetric abrasion loss of 4.1 mm3, and an Izod impact strength of 53.8 kJ·m-2. At the same time, the gas emission during the preparation process is 0.080 mg·m-3. All the data are better than those of the comparative example. After comparative analysis of the data in Table 1, it can be found that the environmental performance of the PVC material prepared in Comparative Example 1 has decreased significantly. This indicates that in Comparative Example 1, the removal of the calcium cross-linking component results in a lack of stable physical cross-linking points within the material, and the loss of spatial network support between the molecular chains, resulting in a loose structure. When subjected to friction or impact, the chain segments are more likely to slip and break, resulting in decreased wear resistance and impact resistance. At the same time, the lack of the calcium component makes it impossible for the system to effectively buffer and neutralize the acidic products during the pyrolysis process, resulting in increased hydrogen chloride gas release and a significant decrease in environmental performance. In addition, the flexible chain segments lack structural constraints at low temperatures, are prone to brittle cracking, and low-temperature resistance is reduced. After comparing and analyzing the data in Table 1, it can be found that the wear resistance of the PVC material prepared in Comparative Example 2 is significantly reduced. This shows that in Comparative Example 2, the removal of the composite inorganic filler weakened the wear-resistant structural support of the material, reduced the surface hardness, and made the chain segments more easily exposed and worn during friction. The absence of the filler also affected the force transmission path. Although the overall flexibility was still maintained, the impact energy dispersion ability was reduced. On the other hand, due to the lack of thermally stable fillers, the material was more easily decomposed by heat, the release of hydrogen chloride increased, and the environmental performance decreased. A comparative analysis of the data in Table 1 reveals that the impact resistance and low-temperature resistance of the PVC material prepared in Comparative Example 3 were significantly reduced. This indicates that the absence of the low-temperature resistance modifier in Comparative Example 3 resulted in reduced chain segment mobility at low temperatures, an increase in the glass transition temperature, premature embrittlement, and a significant decrease in impact resistance. The lack of flexibility adjustment also reduced the ability to absorb transient friction stress, leading to a certain degree of wear resistance degradation. Although other fillers and structures were still present, no significant increase in hydrogen chloride release was observed during pyrolysis, and environmental performance remained stable. However, the lack of flexibility adjustment significantly reduced low-temperature adaptability. Finally, it is explained that the present invention utilizes montmorillonite modified with a silane coupling agent to effectively improve the dispersion and binding ability of magnesium hydroxide, forming a structurally stable composite filler, which provides an interface basis for subsequent reactions; the construction of linear polysiloxane and the introduction of epoxy functional groups give the material good reactivity and low-temperature flexibility, and PVC is cross-linked with the silane structure through mercapto substitution, providing a bridge for subsequent binding with fillers and low-temperature resistant components; at the same time, the precursor generated by the reaction of epoxy soybean oil and glycine is complexed with calcium ions in an alkaline environment to form a bio-based plasticizer, which effectively improves the flexibility of the material. Finally, through the synergistic effect between structural design and functional groups, a stable and high-performance composite system is constructed. Although the division of labor between each step is clear, they are also linked together to form a highly dependent reaction network, which promotes each other, so that the PVC decorative material prepared by the present invention exhibits excellent synergistic performance.

[0058] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A highly cold-resistant and environmentally friendly PVC decorative material, characterized in that: The raw material composition comprises the following parts by weight: 80-100 parts of composite PVC, 8-10 parts of bio-based plasticizer and 6-10 parts of auxiliary additives; The preparation method of the composite PVC comprises the following steps: A1. Add PVC powder, 1,2-ethanedithiol, mercaptopropyltrimethoxysilane, and N,N-dimethylformamide to a reactor. After the reactor temperature is raised to 100-110°C, stir until the reactants are completely dissolved. Then, add tetrabutylammonium bromide to the reactor, keep the temperature and stir for 4-6 hours, and perform post-treatment to obtain modified PVC. A2. Add modified PVC, deionized water and N,N-dimethylformamide into a reactor. Use saturated sodium hydroxide aqueous solution to adjust the pH of the reaction system to 8-10. Then, raise the temperature of the reactor to 70-80°C. Keep warm and stir until the reactants are dissolved. Then, add low-temperature resistant agent and composite filler into the reactor. Keep warm and stir for 1-2 hours. After post-treatment, obtain composite PVC.

2. A highly cold-resistant and environmentally friendly PVC decorative material according to claim 1, characterized in that: In step A1, the amount ratio of the PVC powder, 1,2-ethanedithiol, mercaptopropyltrimethoxysilane, N,N-dimethylformamide and tetrabutylammonium bromide is 8-10g:0.5-0.8g:1-2g:40-50mL:0.3-0.4g; in step A2, the amount ratio of the modified PVC, deionized water, N,N-dimethylformamide, low-temperature resistant agent and composite filler is 8-10g:10-12mL:30-40mL:0.5-0.8g:1.2-1.5g.

3. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 1, characterized in that: The preparation method of the bio-based plasticizer comprises the following steps: B1. Add epoxidized soybean oil, glycine and dimethyl sulfoxide to a reactor, raise the temperature of the reactor to 60-80°C, keep the temperature for reaction for 1-2 hours, and post-treat to obtain a plasticizer precursor; B2. Add the plasticizer precursor, deionized water and dimethyl sulfoxide into the reactor, increase the temperature of the reactor to 50-60°C and use saturated sodium hydroxide aqueous solution to adjust the pH of the reaction system to 8-10, then add calcium chloride into the reactor, keep the temperature and react for 40-60 minutes, and post-treat to obtain the bio-based plasticizer.

4. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 1, characterized in that: The preparation method of the low-temperature resistant agent comprises the following steps: C1. Add 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, trifluoropropylmethylcyclotrisiloxane and N,N-dimethylformamide to a reactor. After the temperature of the reactor is raised to 100-120° C., add sodium hydroxide to the reactor. After keeping the temperature for 4-5 hours, add 1,1,3,3-tetramethyldisiloxane-1,3-diamine to the reactor. Keep the temperature for 2-3 hours, and perform post-treatment to obtain modified polysiloxane. C2. Add modified polysiloxane and N,N-dimethylformamide into a reactor, introduce nitrogen protection, lower the temperature of the reactor to 10-15°C, add m-chloroperbenzoic acid into the reactor, keep the temperature for reaction for 1-2 hours, and post-treat to obtain a low-temperature resistant agent.

5. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 4, characterized in that: In step C1, the amount ratio of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, trifluoropropylmethylcyclotrisiloxane, N,N-dimethylformamide, sodium hydroxide and 1,1,3,3-tetramethyldisiloxane-1,3-diamine is 4-5g:6-8g:50-54mL:0.3-0.5g:1-2g; in step C2, the amount ratio of modified polysiloxane, N,N-dimethylformamide and m-chloroperbenzoic acid is 6-8g:20-24mL:1-2g.

6. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 1, characterized in that: The preparation method of the composite filler comprises the following steps: D1. Add nano-montmorillonite, composite solvent and γ-methacryloxypropyltrimethoxysilane to a reactor. After the temperature of the reactor is raised to 40-60° C., adjust the pH of the reaction system to 4-5 with acetic acid, keep the reaction mixture warm and stir for 1-2 hours, and perform post-treatment to obtain modified montmorillonite. D2. Add modified montmorillonite and deionized water into a reactor, add magnesium chloride into the reactor under stirring, adjust the pH of the reaction system to 10-11 with a protective sodium hydroxide aqueous solution after the addition, stir at room temperature for 60-80 minutes, and post-treat to obtain a composite filler.

7. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 6, characterized in that: In step D1, the amount ratio of nano-montmorillonite, composite solvent and γ-methacryloxypropyltrimethoxysilane is 1-2g:10-12mL:0.1-0.2g, wherein the composite solvent is a mixture of anhydrous ethanol and deionized water in a ratio of 8-10mL:3-4mL; in step D2, the amount ratio of modified montmorillonite, deionized water and magnesium chloride is 1-2g:10-12mL:0.2-0.4g.

8. The highly cold-resistant and environmentally friendly PVC decorative material according to claim 1, characterized in that: The preparation method of the PVC decorative material comprises the following steps: adding composite PVC, a bio-based plasticizer, a heat stabilizer, an antioxidant, a light stabilizer and a lubricant into a melt extruder, melt-extruding the mixture into a mold, and naturally cooling the mixture to room temperature to obtain the PVC decorative material.

9. Application of a highly cold-resistant and environmentally friendly PVC decorative material, characterized in that: The highly cold-resistant, environmentally friendly PVC decorative material according to any one of claims 1 to 8 is used to prepare decorative items for use in high-altitude and low-temperature areas.

Citation Information

Cited By

  • Low-atomization low-odor plasticizer and preparation method thereof

    CN121293770A

  • A low-atomizing low-odor plasticizer and a preparation method thereof

    CN121293770B

  • Alcohol-resistant cosmetic packaging shell material based on polylactic acid modification and preparation method thereof

    CN121554967A

  • Alcohol-resistant cosmetic packaging shell material based on polylactic acid modification and method for preparing the same

    CN121554967B